The Microwave-assisted Extraction of Anthocyanins, Total Phenolic Compounds and the Antioxidant Activity in Morus nigra L. (Black mulberry) Grown in the Da Lat City, Lam Dong Province, Vietnam - Nguyen Hong Khoi Nguyen (Journal of Global Pharma Technology, 2016)
Morus nigra L. (Black mulberry) is a nutritious fruit that contains many bioactive compounds such as anthocyanins, polyhenol and antioxidant activity. The microwave-assisted extraction method (MAE) is an advanced method with due to its advantages of short extraction time and lower solvent consumption. The objective of this research is to find the appropriate conditions to extract the highest contents of anthocyanin, polyphenol and antioxidant activity in black mulberry by MAE method. The pH-differential method is used to determine the anthocyanin content, the polyphenol content is determined by the Folin-Ciocalteu method and the antioxidant activity is determined by the DPPH method. The highest contents of these coumponds were obtained as follows anthocyanin contents 128.07 mg/L, polyphenol contents 4305.38 mg/L and antioxidant activity 2715.68 μmol/L when extracted under conditions of concentration of ethanol 60o, solid to solvent ratio 1:30, microwave power 600W, microwave-assisted extraction time 2 minutes.Keywords: Black mulberry, Anthocyanin, Polyphenol, Antioxidant activity, Microwave-assisted extraction.